2014
DOI: 10.1148/radiol.13130940
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation of Hepatocellular Carcinoma as First-Line Treatment: Long-term Results and Prognostic Factors in 162 Patients with Cirrhosis

Abstract: RFA is a safe and effective first-line treatment for early-stage HCC, with a 5-year survival rate of 67.9%. High serum α-fetoprotein level, advanced Child-Pugh class, and presence of portosystemic collateral vessels had a significant negative effect on overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
229
5
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(265 citation statements)
references
References 44 publications
24
229
5
7
Order By: Relevance
“…A reported cumulative rate of tumor recurrence after RFA in patients with HCC is 60-80%. 22,23 With a median follow up of nearly 10 years, local RFA site recurrence was found in 15.6% of our HCC patients. In this study, we initially used an RF 2000 ® Radiofrequency Generator for a year, before updating our generator to the newer version (higher power) of RF 3000 ® Radiofrequency Generator (Boston Scientific, Natick, MA, USA).…”
Section: Discussionmentioning
confidence: 84%
“…A reported cumulative rate of tumor recurrence after RFA in patients with HCC is 60-80%. 22,23 With a median follow up of nearly 10 years, local RFA site recurrence was found in 15.6% of our HCC patients. In this study, we initially used an RF 2000 ® Radiofrequency Generator for a year, before updating our generator to the newer version (higher power) of RF 3000 ® Radiofrequency Generator (Boston Scientific, Natick, MA, USA).…”
Section: Discussionmentioning
confidence: 84%
“…24 This treatment mimics human clinical scenarios of both complete and incomplete ablation, as ablation was more effective in small tumors when compared to the effects of ablation on larger tumors (Fig. 4).…”
Section: Discussionmentioning
confidence: 98%
“…It was apparently not suitable for these patients with liver tumor size of 4 cm to receive percutaneous ethanol injection only. (3) This approach likely influenced the local tumor progression rate in the RFA group. …”
Section: To the Editormentioning
confidence: 99%
“…(1) Indeed, with improved devices and techniques, many studies have reported encouraging results, including complete ablation and survival rates of RFA in treating HCC lesions >3 cm. (2,3) In our study, patients with incomplete ablation after two sessions of the same technique were considered treatment failures and were further treated by percutaneous ethanol injection, microwave, RFA, cryoablation, or surgery, as appropriate. Our study was performed between February 2008 and October 2013, and six patients in the RFA group did not undergo an additional course of RFA treatment as they declined the option of RFA or cryoablation for additional treatment.…”
Section: Replymentioning
confidence: 99%